Realization Method for Detection on Arc Based on CCD - Liu, Qing Min; Zhang, L.; Li, Xue (Applied Mechanics and Materials, 2014)
s: Arc detection is difficult for processing, assembly and testing of industrial production because of limitations of detection methods, algorithms and instruments. The least-squares algorithm is used to fit data in circle detection. The application of conventional least-squares algorithm is limited, as roundness error is bigger, precision is lower. For detecting arc with data points of non-uniform distribution, improved least-squares algorithm, developed an analysis algorithm for assessing the minimum zone roundness error. Center and radius can be solved, without iteration and truncation error. Using the discrete data instances verified different roundness error evaluation methods. Visual measurements have been carried out using the proposed methods. Calculated results using the four kinds of roundness error evaluation methods (Figure 7-10). Ball diameter errors are-0.0245mm、0.0176mm、-0.1052mm and 0.302mm, roundness errors are 0.07mm、0.063mm、0.078mm and 0.146mm. The improved least-squares algorithm and the minimum zone algorithm are suitable for distributed data of all kinds situations, particularly suitable for the realization of machine vision inspection system, fast speed, high precision, wide application.